Performance-Improved Broadcast-and-Select Optical Switch Module Based on EAM-Gate Array - Y. Muranaka; T. Segawa; Y. Ogiso; T. Fujii; R. Takahashi (IEEE Photonics Journal)
Performance improvement of a broadcast-and-select (B&S) optical switch based on an electro-absorption modulator (EAM)-gate array is presented. The introduction of a novel spot-size converter (SSC) with an easy fabrication process reduced the optical coupling loss between the switch's waveguide array and input/output fibers and enhanced the optical-coupling tolerance for misalignment as the SSC properly expands the waveguide's mode field as well. In addition, the electrical crosstalk, which causes undesirable changes in the output power from different switch ports, was suppressed by the simple addition of a grounded electrode that covers the surface of passive waveguides, instead of employing a complicated regrowth process, as is usually done for electrical isolation between EAMs. A 4 $×$ 4 B&S optical switch module has been fabricated with these improvements and has successfully exhibited low insertion loss (< 15.3 dB), little variation in insertion loss, a fast switching time (< 8 ns), low power consumption (< 3 W), and a high extinction ratio (∼50 dB).